Exploring The Efficacy Of Polyherbal Formulations In Hepatoprotection: A Comprehensive Review Of Phytomedicines (Journal of Namibian Studies : History Politics Culture, 2023)
Alternative medicinal techniques, especially polyherbal formulations with hepatoprotective characteristics, have attracted a lot of attention due to the increasing incidence of liver illnesses. By analysing their phytochemical components, modes of action, and clinical results, this study seeks to assess the effectiveness of several polyherbal formulations used for hepatoprotection. This review synthesises information on the efficacy of these formulations in protecting liver health and minimising liver damage by analysing a variety of research, including both preclinical and clinical trials. Some people think that the synergistic effects of combining several herbal constituents in a polyherbal composition make them more effective. This study focusses on important phytomedicines, including the functions of their active components (such as terpenoids, saponins, and flavonoids) in preventing inflammation, regenerating damaged liver tissue, and oxidative stress. The hepatoprotective benefits of these formulations, such as improved liver function biomarkers and modification of hepatic enzyme activity, are explored in detail.Moreover, the evaluation delves into the formulations' safety profiles, including possible side effects and interactions with traditional medicines. It delves further into the topic by investigating the reasons for the discrepancies in claimed effectiveness among trials, including formulation composition, dose, and research design, among others. Ultimately, this review delves into the existing research on polyherbal hepatoprotective formulations, shedding light on their practical use in the clinic and their promise as supplementary therapies for liver diseases. It highlights the need of doing more studies to identify potential side effects, standardise formulations, and optimise therapy techniques.